Monocyte to High-Density Lipoprotein Ratio: A Novel Predictive Marker of Disease Severity and Prognosis in Patients With Neuromyelitis Optica Spectrum Disorders - Zhang, Jinwei; Li, Yanfei; Zhou, Yongyan; Wang, Kaixin; Pan, Chunyang; Zhao, Yi; Xie, Haojie; Duan, Ranran; Gong, Zhe; Jia, Yanjie (Frontiers in Neurology, 2021)
Background and Purpose: To investigate the association of monocyte to high-density lipoprotein ratio (MHR) with disease severity and prognosis in patients with neuromyelitis optica spectrum disorders (NMOSD). Methods: This retrospective study included 125 patients with NMOSD. Demographic and clinical parameters, including the MHR, were assessed. The initial Expanded Disability Status Scale (EDSS) score and relapse rate were used to evaluate disease severity and prognosis, respectively. Correlations between MHR and disease severity and relapse rate were analyzed. The predictive value of MHR for prognosis was evaluated using receiver operating characteristic (ROC) curve analysis. Results: Compared with the low MHR group, the initial EDSS score (median 4.5% vs. 5.5%, P=0.025) and relapse rate (51.61% vs. 30.16%, P=0.015) were significantly higher in the high MHR group. MHR was positively correlated with the initial EDSS score (r=0.306, P=0.001). Multivariate analysis showed that MHR was significantly associated with severity (odds ratio=7.90, 95% confidence interval [CI]=1.08-57.82, P=0.041), and it was a significant predictor of disease prognosis (hazard ratio=3.12, 95% CI=1.02-9.53, P=0.046). The median relapse interval of the high MHR group was 24.40 months. When the MHR was higher than 0.565, the risk of relapse was high (sensitivity, 33.3%; specificity, 91.9%; area under the ROC curve, 0.642 (95% CI=0.54-0.74, P=0.007)). Conclusion: MHR is a novel predictive marker of disease severity and prognosis in patients with NMOSD. Early monitoring and reduction of MHR may allow earlier intervention and improved prognosis.